2012
DOI: 10.4049/jimmunol.1101788
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Promoter and the Transcriptional Regulation of theLipoxin A4 Receptor(FPR2/ALX) Gene in Human Monocytes and Macrophages

Abstract: The lipoxin A4 receptor FPR2/ALX plays an important part in host defense and inflammation. The receptor binds structurally diverse agonistic ligands, which mainly regulate chemotaxis and activation of leukocytes. However, little is known about the promoter region of the FPR2/ALX gene and its transcriptional regulation in leukocytes. We identified two TATA-less promoter regions, separated by 224 bp, that drive the expression of FPR2/ALX in macrophages. Both promoter regions increased transcription in a reporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 71 publications
4
32
0
Order By: Relevance
“…We have previously shown that the FPR2/ALX receptor is absent in primary human macrophages (22), suggesting that LXA4 proresolution actions may be mediated by other receptors in these cells (40,41), and we show in this article that RvD1 signaling in human macrophages is mediated by GPR32, involving calcium release from intracellular stores. In contrast, RvD1 signaling in human neutrophils differs from that of macrophages.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…We have previously shown that the FPR2/ALX receptor is absent in primary human macrophages (22), suggesting that LXA4 proresolution actions may be mediated by other receptors in these cells (40,41), and we show in this article that RvD1 signaling in human macrophages is mediated by GPR32, involving calcium release from intracellular stores. In contrast, RvD1 signaling in human neutrophils differs from that of macrophages.…”
Section: Discussionmentioning
confidence: 75%
“…Bars indicate the mean and SD of three independent experiments. *p , 0.05 compared with basal migration of macrophages without stimuli, levels as we have previously done for other G protein-coupled receptors triggered by lipid mediators (22,25,27). GPR32 is transcribed and expressed on the surface of resting macrophages (Fig.…”
Section: Grp32 Is Expressed In Resting M1 and M2 Primary Human Macrmentioning
confidence: 71%
See 2 more Smart Citations
“…Previous studies revealed that IFN-γ up-regulates FPR2/ALXmRNA in microglia from mice [19], and in human enterocytes [20] and macrophages [21]. In addition, FPR2/ALX has been shown to be up-regulated by IL-13 [20], a cytokine also produced mainly In contrast to the up-regulation of FPR2/ALX mRNA levels in THP-1 cells after pro-inflammatory stimuli, but in line with the results of activated CD4 + cells /macrophage co-cultures (Fig 1B), the expression of the BLT 1 receptor once more displayed a different profile.…”
Section: Ifn-γ γ γ γ Up-regulates Fpr2/alx Mrna But Down-regulates Blmentioning
confidence: 99%